2008
DOI: 10.1002/jbm.b.31240
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and use of pHEMA microbeads with human EA.hy 926 endothelial cells

Abstract: Cancer has become a major problem in public health and the resulting bone metastases a worsening factor. Facing it, different strategies have been proposed and mechanisms involved in tumor angiogenesis are being studied. Enhanced permeability retention (EPR) effect is a key step in designing new anticancer drugs. We have prepared poly 2-hydroxyethyl methacrylate (pHEMA) microbeads to target human endothelial EA.hy 926 cells, a cell line derived from human umbilical vein endothelial cells. Microbeads were synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In this study, microbeads containing Nile red were prepared as a fluorescent tracer for endothelial cells and macrophages. Microbeads can be rapidly trapped by endothelial cells (particularly in the case of rapid angiogenesis) and phagocytosed by macrophages in the stroma of the tissues [19]. This as been recognized as the Enhanced Permeability Retention effect [41,43,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, microbeads containing Nile red were prepared as a fluorescent tracer for endothelial cells and macrophages. Microbeads can be rapidly trapped by endothelial cells (particularly in the case of rapid angiogenesis) and phagocytosed by macrophages in the stroma of the tissues [19]. This as been recognized as the Enhanced Permeability Retention effect [41,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Microbeads of pHEMA labeled with Nile red were prepared according to our previously reported protocol with minor modifications [18,19]. Briefly, microbeads were prepared by an emulsion precipitation method by using the monomer HEMA (2-hydroxyethyl methacrylate).…”
Section: Preparation Of Phema Microbeadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger particles, such as the composite nanoparticles in a polymer shell/carrier, as the commercially-available micron-sized beads used here, would be preferable since a stronger magnetic force (proportional to particle’s mass) can be generated as compared to nano-particles. In this regard, the uptake by EC of hydrogel microspheres (Nguyen et al 2009), microparticles (Terrisse et al 2010) and microbeads (Nyangoga et al 2009) have been reported before. Herein, we tested the labeling of the EC with relatively larger magnetic microbeads.…”
Section: Introductionmentioning
confidence: 62%
“…Other areas of the biomedical field have been accessed by PHEMA drug carriers, namely cancer treatment [ 91 , 93 ] and neurologic diseases treatment [ 94 ].…”
Section: Polymers In Drug Delivery Systemsmentioning
confidence: 99%